Residential Neighborhood Crime Control Project: Hartford, Connecticut, 1973, 1975-1977, 1979 - Fowler, Floyd J. ([Verlag nicht ermittelbar], 1984)
This data collection contains responses to victimization surveys that were administered as part of both the planning and evaluation stages of the Hartford Project, a crime opportunity reduction program implemented in a residential neighborhood in Hartford, Connecticut, in 1976. The Hartford Project was an experiment in how to reduce residential burglary and street robbery/purse snatching and the fear of those crimes. Funded through the Hartford Institute of Criminal and Social Justice, the project began in 1973. It was based on a new "environmental" approach to crime prevention: a comprehensive and integrative view addressing not only the relationship among citizens, police, and offenders, but also the effect of the physical environment on their attitudes and behavior. The surveys were administered by the Center for Survey Research at the University of Massachusetts at Boston. The Center collected Hartford resident survey data in five different years: 1973, 1975, 1976, 1977, and 1979. The 1973 survey provided basic data for problem analysis and planning. These data were updated twice: in 1975 to gather baseline data for the time of program implementation, and in the spring of 1976 with a survey of households in one targeted neighborhood of Hartford to provide data for the time of implementation of physical changes there. Program evaluation surveys were carried out in the spring of 1977 and two years later in 1979. The procedures for each survey were essentially identical each year in order to ensure comparability across time. The one exception was the 1976 sample, which was not independent of the one taken in 1975. In each survey except 1979, respondents reported on experiences during the preceding 12-month period. In 1979 the time reference was the past two years. The survey questions were very similar from year to year, with 1973 being the most unique. All surveys focused on victimization, fear, and perceived risk of being victims of the target crimes. Other questions explored perceptions of and attitudes toward police, neighborhood problems, and neighbors. The surveys also included questions on household and respondent characteristics.